DAMPAK KEBIASAAN MINUM-MINUMAN KERAS PADA MAHASISWA KABUPATEN KAPUAS HULU - Pranata, Joni; Bahari, Yohanes; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
The title of this study is "The impact of the habit of social irregularities of drinking alcohol at the students of Kapuas Hulu Regency". A general problem of research is how the impact of drinking habits at the students of Kapuas Hulu Regency on Jl. Budi Karya Pontianak. The purpose of this study is to know and describe the impact of drinking habits on lectures and interactions of Kapuas Hulu students. The approach used is qualitative approach with descriptive method. Data collection techniques used are observation techniques, interviews, and lectures documentation, with data collection tools such as observation guides, interview guides, and documentation. The analysis in this study is presented descriptively qualitative by using informans as many as 16 people, consisting of 13 students who do social deviation drinking alcohol as a subject and 3 people as crosschek community. The results of this study indicate that the habit of social deviation drinking badly affect the lectures and interactions of Kapuas Hulu Kapuas students with the community. Based on the observations, interviews, and documentation that the researchers have conducted, proves that the habit of social deviation from drinking can be bad for the lectures and interaction of Kapuas Hulu students with the community.Â Keywords: Social Deviance, Habit ofÂ  Drinking Â